2009
DOI: 10.1002/ibd.20946
|View full text |Cite
|
Sign up to set email alerts
|

Fecal dimeric M2-pyruvate kinase (tumor M2-PK) in the differential diagnosis of functional and organic bowel disorders

Abstract: Tumor M2-PK is able to differentiate organic from functional bowel disease but has a lower sensitivity, specificity, and predictive value than calprotectin. Further studies are required, alone or in combination with other markers, before its usefulness in this setting can be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 20 publications
0
16
1
Order By: Relevance
“…8 This data was slightly different to the data obtained in this study, which could possibly be caused by the different study design being used. From this data, we could evaluate that the sensitivity value was 86.2% which showed that this examination was quite sensitive to detect the presence of intestinal that this examination was quite good to determine if a patient was healthy if the examination result was negative.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…8 This data was slightly different to the data obtained in this study, which could possibly be caused by the different study design being used. From this data, we could evaluate that the sensitivity value was 86.2% which showed that this examination was quite sensitive to detect the presence of intestinal that this examination was quite good to determine if a patient was healthy if the examination result was negative.…”
Section: Discussioncontrasting
confidence: 53%
“…1,2,3,4 However, in several other studies, M2-PK is proved 5,6,7 Other studies comparing the level of M2-PK in patients M2-PK. 8 If examination using protein marker from bowel, then invasive examinations, such as endoscopy, which require high cost and cause inconvenience can be conducted in more selective manner. This is diagnose disease properly and patient becomes more comfortable and does not need to spend high cost for examinations.…”
Section: Introductionmentioning
confidence: 99%
“…In a study in children with GI tract symptoms faecal M2-PK had a sensitivity of 71% and a specificity of 97% for distinguishing between those with IBD and those without any detectable pathology 23. In a study of 105 gastroenterology outpatients and 94 controls faecal M2-PK had a sensitivity of 93% and a specificity of 92% compared to 67% and 88% respectively for calprotectin 24. In an attempt to find a marker that could predict failure to respond to steroid therapy in severe paediatric UC, Turner et al studied faecal calprotectin, lactoferrin, M2-PK and S100A12.…”
Section: Dimeric Pyruvate Kinasementioning
confidence: 96%
“…Furthermore, higher levels were evident in individuals with active IBD than in those with quiescent disease. In a further study, M2-PK was assessed in 105 adults presenting with undifferentiated gastrointestinal symptoms and 94 healthy controls [9]. The 14 adults subsequently diagnosed with organic diseases (only 10 with IBD) had higher fecal concentrations of M2-PK than those with functional symptoms or the controls.…”
Section: M2-pkmentioning
confidence: 99%